2023
DOI: 10.24248/eahrj.v7i1.714
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pattern, and Management Outcomes of Chest Injury at Kilimanjaro Christian Medical Centre

Abstract: Background: Chest trauma is a major cause of morbidity and mortality in the region. Lacking data in our environment has been a challenging part of knowing the burden of the problem. Long hospital stays and associated injuries are an essential measure of morbidity. The study results will provide a basis for planning prevention strategies and establishment of treatment protocols. Objectives: To determine the prevalence, pattern, and management outcomes of chest injury pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The pooled effect of four studies [ 26 , 34 , 39 , 40 ] revealed that individuals aged over 50 had 3.5 times higher odds (AOR 3.5; 95% CI: 1.19, 10.35) of mortality compared to those under 20. Similarly, the combined findings of three studies [ 26 , 39 , 40 ] indicated that a time interval between injury and admission of 2–6 h was associated with 3.9 times higher odds of mortality (AOR 3.9; 95% CI: 2.04, 7.51) compared to admission within less than 2 h. Additionally, the amalgamated results of three studies [ 26 , 31 , 40 ] demonstrated that associated injuries with the head and neck carried six times higher odds of mortality (AOR 6.28; 95% CI: 3.00, 13.15) than their counterparts. Furthermore, the combined effect of two studies [ 26 , 40 ] showed that associated spinal injuries were associated with 7.8 times higher odds of mortality (AOR 7.86; 95% CI 3.02, 19.51) compared to cases without spinal injuries.…”
Section: Meta-analysis Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The pooled effect of four studies [ 26 , 34 , 39 , 40 ] revealed that individuals aged over 50 had 3.5 times higher odds (AOR 3.5; 95% CI: 1.19, 10.35) of mortality compared to those under 20. Similarly, the combined findings of three studies [ 26 , 39 , 40 ] indicated that a time interval between injury and admission of 2–6 h was associated with 3.9 times higher odds of mortality (AOR 3.9; 95% CI: 2.04, 7.51) compared to admission within less than 2 h. Additionally, the amalgamated results of three studies [ 26 , 31 , 40 ] demonstrated that associated injuries with the head and neck carried six times higher odds of mortality (AOR 6.28; 95% CI: 3.00, 13.15) than their counterparts. Furthermore, the combined effect of two studies [ 26 , 40 ] showed that associated spinal injuries were associated with 7.8 times higher odds of mortality (AOR 7.86; 95% CI 3.02, 19.51) compared to cases without spinal injuries.…”
Section: Meta-analysis Resultsmentioning
confidence: 93%
“…Of these 21 published original studies that reported the proportion of mortality, four were conducted in Ethiopia [ 26 , 29 , 39 , 40 ], and the majority of studies (nine) were conducted in Nigeria [ 4 , 25 , 27 , 28 , 33 37 ]. The other studies were conducted in Tanzania (three) [ 30 , 31 , 43 ], South Africa (two) [ 41 , 42 ], Cameroon (one) [ 32 ], Senegal (one) [ 44 ], and Sudan (one) [ 38 ]. Most studies were conducted with a cross-sectional design (thirteen) [ 4 , 25 – 27 , 29 , 31 , 32 , 36 , 39 – 42 , 44 ], and the fewest were conducted via prospective cohort studies (eight) [ 28 , 30 , 33 35 , 37 , 38 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation